2015
DOI: 10.1111/1365-2478.12255
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of seismic reflections from faults in a crystalline environment, Schneeberg, Germany

Abstract: A B S T R A C TWe present an approach for analysing seismic reflections from faults in a crystalline hard rock environment. We analysed 3D seismic reflection data for geothermal reservoir characterization acquired in the Erzgebirge Region, Germany. The seismic image derived from this data set revealed two main features: a less pronounced reflector corresponding to a steeply dipping major fault zone Roter Kamm and a group of pronounced reflectors attributed to the existence of conjugate mineralized faults. We a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 12 publications
2
6
0
Order By: Relevance
“…After some initial testing with the constant velocity model, we concluded that qualitatively best results are obtained from CBVFM among other approaches (e.g., FVM alone). This was also suggested by previous studies performed in crystalline environments (e.g., [12,13,16,30]). Therefore, here we focus on the results of the CBFVM approach.…”
Section: Specialized Kirchhoff Presdmsupporting
confidence: 85%
See 2 more Smart Citations
“…After some initial testing with the constant velocity model, we concluded that qualitatively best results are obtained from CBVFM among other approaches (e.g., FVM alone). This was also suggested by previous studies performed in crystalline environments (e.g., [12,13,16,30]). Therefore, here we focus on the results of the CBFVM approach.…”
Section: Specialized Kirchhoff Presdmsupporting
confidence: 85%
“…Also, as discussed earlier, result depends on the power value "p" (Equation 4), and therefore we also tested two different values of p = 1 and p = 2 (Figure 8). was also suggested by previous studies performed in crystalline environments (e.g., [12,13,16,30]). Therefore, here we focus on the results of the CBFVM approach.…”
Section: Specialized Kirchhoff Presdmsupporting
confidence: 75%
See 1 more Smart Citation
“…A detailed analysis of the reflection coefficients and the characteristics of both the Roter Kamm and the conjugate fault reflectors can be found in Schreiter et al . ().…”
Section: Resultsmentioning
confidence: 97%
“…Recently, Hloušek et al (2015a) and Schreiter et al (2015) report on the processing and interpretation, respectively, of a 3D survey of approximate areal extent 10 × 13 km that was conducted in 2012 in western Erzgebirge near the city of Schneeberg, Germany (see also Ahmed et al, 2015;Lüschen et al, 2015). The aim of the project was to characterize the major fracture zones in the crystalline rock at approximately 4-5 km depth.…”
Section: Enhanced Geothermal Systemsmentioning
confidence: 99%